Risky sexual behaviors and their associated factors within high school students from Collège Saint André in Kigali, Rwanda: An institution-based cross-sectional study - Ndagijimana, Emmanuel; Biracyaza, Emmanuel; Nzayirambaho, Manasse (Frontiers in Reproductive Health, 2023)
Background Risky sexual behaviors (RSBs) remain public health concerns in adolescents from sub-Saharan Africa (SSA), and these practices may increase vulnerability to reproductive health problems if no early healthcare strategies are implemented. While previous studies reported that adolescents are engaged in these RSBs due to diverse influences such as the teenage stage, urbanization, and change in the environment they experience, there is a shortage of studies on RSB among adolescents in SSA. This study assessed the magnitude of RSBs and the RSB-associated factors among in-school adolescents. Methods School-based cross-sectional study was conducted among 263 Saint Andre school students in Kigali, Rwanda, from July 3, 2020, to September 30, 2020. Systematic random sampling techniques were employed. All data were entered into Epi-Data and analyzed using SPSS version 25. Chi-square tests and multivariable logistic regression analyses were applied to determine factors associated with risky sexual behaviors. Confidence intervals (CIs) of 95% and 5% for statistical significance were maintained. Results Of 263 participants, 109 (41%) experienced RSB in their lifetime. Among them, 66 respondents (60.55%) utilized contraceptive methods to prevent sexual and reproductive problems that can be caused by unprotected sexual intercourse. The students who experienced domestic violence had increased odds of experiencing RSB [odds ratio (OR) = 4.22; 95% CI: 1.6–11.23] than their counterparts. Those in grade 11 (OR = 2.68; 95% CI: 1.06–6.78) and grade 12 (OR = 4.39; 95% CI: 1.82–10.56) were more likely to practice RSB than those in grade 10. Alcohol users were almost more likely to experience RSB (OR = 3.9; 95% CI: 1.97–5.5) than their counterparts. Those who lived away from their biological parents had higher likelihood of experiencing RSB (OR = 2.5; 95% CI: 1.14–4.42) than those who lived with one or both parents. Students who experienced peer pressure were more likely to engage in RSB (OR = 3.9; 95% CI: 2.01–7.51) than their counterparts. Conclusion Promoting specific intervention programs built upon the factors associated with RSB among high school students needs to be prioritized.